British Economic Growth, 1270-1870: an output-based approach - Stephen Broadberry; Bruce Campbell; Alexander Klein; Mark Overton; Bas van Leeuwen (University of Kent, School of Economics, 2012)
This paper reconstructs GDP from the output side for medieval and early modern Britain. In contrast to the long run stagnation of living standards suggested by daily real wage rates, output-based GDP per capita exhibits modest but positive trend growth. One way of reconciling the two series is through variation in the annual number of days worked, but there are also reasons to doubt the representativeness of the sharp rise and fall of daily real wage rates in the late middle ages, which creates the impression of no trend improvement of living standards.
Keywords: O11; O40; E01; 330; Economic Development; Economic Growth; National Income